Drgania Ustalone Przestrzennych Tras Prętowych - Łukowiak, M. (Engineering Transactions, 1967)
In Ref. [1] were described computation methods of bar systems, the mechanical schemes of which approach those of power pipelines. The author proposes a method for determining the frequency of natural vibration of a bar system and the internal forces and moments produced by mechanical actions. The way in which the bar system is supported is arbitrary and elastic elements may occur on its length in the form of hinges or compensators. The matrix notation is used thus facilitating computer programming.